Reliability and validity of the modified functional reach test at the sub-acute stage post-stroke - Katz-Leurer, Michal; Fisher, Iris; Neeb, Martin; Schwartz, Isabella; Carmeli, Eli (Disability and rehabilitation, 2009)
The first aim of this study was to evaluate the within-session reliability of sitting balance measures by assessing forward and lateral reach while sitting in both healthy subjects and patients post- stroke. The second aim was to evaluate the ability to document change in reaching while sitting over time in patients post-stroke. The third aim was to compare sitting balance results by the modified functional reach test (MFRT) to the Balance Master (BM), motor and function assessments. Data were collected on two occasions: Two to three weeks post-event and again six weeks later. On each occasion within-session reliability was tested using the intra-class correlations (ICC). The tests were performed three times; the second and third attempts were compared in order to test the within-session reliability. For assessing the concurrent validity, the MFRT results were compared with the BM results, Stroke Assessment Scale (SAS) and the Functional Independence Measure (FIM) score using Pearson correlations. In-patient rehabilitation department. Patients after a first ischemic stroke 14 - 21 days post-event were recruited from the inpatient rehabilitation department at Hadassah University Hospital, Jerusalem, Israel. Excluded were patients with brain stem lesions and/or bilateral signs or hemorrhagic events as diagnosed by Computerized Tomography, patients with Mini-Mental State Examination < 20, those who were not able to sit unsupported for 10 sec and those who could stand without support for more than 30 sec. The MFRT, performed while sitting in forward and sideward directions. The MFRT in all directions on both occasions exhibited high reliability (intra-class correlation coefficient range, 0.90 - 0.97). The responsiveness to the paretic side was high (effect size 0.80) and moderate for the forward and non-paretic side (effect size 0.57 - 0.60). A significant moderate correlation was found between MFRT and BM on both occasions. The MFRT while sitting can be reliably measured and may serve as a useful outcome measure in individuals with stroke 2 - 8 weeks post-event.